Elizabeth R. Gebhard and Timothy E. Gregory (eds). Bridge of the Untiring Sea: The Corinthian Isthmus from Prehistory to Late Antiquity - Ippolito, Francesca (Journal of Greek Archaeology, 2018)
This volume is a collection of papers delivered at a conference celebrating 55 years (1952-2007) of archaeological works at the Corinthian Isthmus. After an Introduction, which includes Early Iron Age through 5th century AD written sources mentioning Corinth and the Isthmus and a brief geographical and topographical description of the region, the authors summarize the research history, from the first recordings by travelers in the 15th century.